Deterministic program rerun within a virtual machine - Pavel Dovgalyuk (Труды Института системного программирования РАН, 2018)
The paper describes a technology that allows to capture and rerun scripts of program execution within a virtual machine. This technology enables to debug programs deterministically and may be use in future for implementation of different mechanisms of dynamic program analysis and reverse debugging.